A method for surface treatment of electrolytic copper foil

CN115386926BActive Publication Date: 2026-10-09JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211010836.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-23
Publication Date
2026-10-09
Estimated Expiration
2042-08-23

AI Technical Summary

Technical Problem

虽然较高的粗糙度可以保证优异的抗剥离性能,但是高粗糙度下趋肤效应对信号传输的不利影响也不可忽略

Benefits of technology

[0034] The coarsened particles formed on the treated surface by the method of this invention significantly increase the specific surface area of ​​the electrolytic copper foil, enhancing both mechanical and chemical bonding. Electrolytic copper foil produced by this method has a surface roughness Rz not exceeding 2.0 μm, a root mean square surface roughness Sq not exceeding 1.0 μm, an interface expansion area ratio Sdr > 40%, and a peak curvature Spc > 80 mm. -1 Peak density Spd > 30000 mm -2 This method improves the surface roughness, peel resistance, and signal transmission performance of electrolytic copper foil to a certain extent. The peel strength of a 35μm finished foil laminated with a prepreg at a glass transition temperature of 200℃ is >0.76 kgf/cm. When copper foil produced by the method provided in this invention is laminated with polyphenylene ether resin to form a copper-clad laminate, the insertion loss of the resulting PCB material at 25GHz can reach -0.9 dB/inch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115386926B_ABST
    Figure CN115386926B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of electrolytic copper foil surface treatment method, comprising: (1) using pulse power to the light surface of electrolytic foil is carried out electrochemical polishing pretreatment;(2) by leveling agent assisted direct current electrochemical deposition forms roughening primer layer, obtains the electrolytic copper foil with roughening primer layer;(3) by additive assisted pulse electrochemical deposition is formed on the surface of roughening primer layer second roughening layer;(4) finally, in turn, by electrochemical deposition in the treatment surface and non-treatment surface of electrolytic copper foil barrier layer and anti-oxidation layer, coating silane coupling agent obtains finished product foil;Wherein, roughening particle is formed on the surface of second roughening layer.The roughening particle formed in the treatment surface of the method of the present application, the specific surface area of electrolytic copper foil treatment surface is significantly increased, while enhancing mechanical bonding also improves chemical bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of printed circuit boards, and specifically relates to a method for surface treatment of electrolytic copper foil. Background Technology

[0002] Information technology, along with materials technology and energy technology, are considered the three pillar technologies of the 21st century. Printed circuit boards (PCBs) are indispensable key hardware in the information industry, widely used in various aspects of daily life, from portable electronic devices to new energy vehicles. As one of the core raw materials of PCBs, electronic circuit copper foil plays a crucial role in the functional realization of PCBs. Depending on the production method, electronic circuit copper foil can be divided into rolled copper foil and electrolytic copper foil. Rolled copper foil has excellent bending resistance and is mostly used in flexible circuit boards. Due to processing cost limitations, the production capacity of rolled copper foil cannot fully meet the needs of the PCB industry. Electrolytic copper foil, through an electrochemical reaction, transforms Cu... 2+ The conversion of ions into elemental copper can significantly reduce the production cost of copper foil for electronic circuits.

[0003] In recent years, the widespread adoption of advanced electronic information technologies, such as high-speed servers and 5G communications, has effectively driven the rapid development of the PCB industry. Thinning and high integration have gradually become the mainstream trends in the development of high-frequency, high-speed PCBs. With the reduction in the thickness of the dielectric layer on PCB boards and the increase in the glass transition temperature, high-frequency, high-speed PCBs place higher demands on the copper foil of electronic circuits.

[0004] There are four types of signal loss during transmission on a PCB, as shown in Formula 1-1.

[0005] α T =α c +α D +α R +α L (Formula 1-1)

[0006] Where, α T For transmission loss, α C For conductor loss, α D For dielectric loss, α R For radiation loss, α L This is leakage loss. Generally, signal transmission loss in a PCB is mainly due to conductor loss α. C and dielectric loss α D The effect of conductor loss α. C It is related to the roughness Rz of the copper foil, while the dielectric loss α D Then, the frequency f of the signal and the dielectric constant D are related. k and dielectric loss factor D fThe value is closely related. For high-speed PCB products, signal transmission loss is an important indicator. This is because conductor losses α occur during signal transmission on the PCB. C The surface roughness Rz of the copper foil is related to the signal transmission loss of the PCB. Therefore, reducing the surface roughness Rz of the copper foil plays a crucial role in reducing signal transmission loss, improving the signal transmission performance of high-speed PCBs, and enhancing the signal integrity of PCB products. As the signal frequency f gradually increases, the skin effect in the signal transmission line also gradually increases, and a larger proportion of the current will be concentrated in the surface or near-surface region of the signal transmission line. The skin depth (δ) during signal transmission... s The skin depth is affected by the line's permeability (μ), conductivity (σ), and signal frequency (f). s The relationship between the ) and each influencing factor is shown in Formula 1-2.

[0007]

[0008] For PCBs that use copper as the signal transmission carrier, the skin depth (δ) s The skin depth δ is mainly affected by the signal frequency (f). As shown in Equation 1-2, the higher the signal frequency f, the greater the skin depth δ. s The smaller the skin depth, the more concentrated the current is in the surface region of the circuit. At a temperature of 20℃ and a frequency of 1GHz, the skin depth δ of copper... s The skin depth δ of copper is 2.09 μm; when the signal frequency f reaches 10 GHz, the skin depth δ of copper is... s It's only 0.66μm. The roughness of ordinary copper foil is around 5.0μm, and 5G signals are primarily transmitted within this rough layer. Uneven current distribution in the circuit causes increased resistance. This increased resistance leads to a higher proportion of high-frequency signals being lost as heat within the copper foil, ultimately resulting in significant signal attenuation. Therefore, to ensure signal integrity, the adverse effects of the skin effect on signal transmission must be minimized. In conclusion, high-speed, high-frequency PCBs, which are sensitive to signal transmission loss, require electronic circuit copper foils with a very low roughness Rz.

[0009] Similar to traditional PCB manufacturing, high-speed, high-frequency PCBs use copper-clad laminate (CCL) as raw material for processing and treatment. CCL is formed by laminating prepreg and copper foil through hot pressing. During the hot pressing process, the prepreg undergoes a glass transition and a physical-chemical reaction occurs between it and the copper foil, ultimately forming a bonded whole. The bonding strength between the electrolytic copper foil and the resin substrate directly determines the processability of the CCL and the reliability of the PCB product. To enhance the bonding strength between the copper foil and the resin substrate, the electrolytic copper foil usually needs to be roughened. Increasing the roughness of the copper foil improves the mechanical anchoring effect between the copper foil and the resin substrate, thereby enhancing the bonding strength between the two materials. Therefore, the effect of copper foil roughening treatment plays a crucial role in the processability and reliability of downstream products. The rough surface of raw electrolytic copper foil often has an undulating, mountain-like microstructure, possessing a certain roughness, significantly higher than that of a smooth surface. Traditionally, surface treatment of electrolytic copper foil is mostly performed on the rough surface to fully utilize its roughness. However, high-speed, high-frequency PCBs require minimizing the roughness of the copper foil while ensuring sufficient peel resistance. Therefore, surface treatment technology using the smooth surface of electrolytic raw copper foil as the treated surface has emerged. Because the smooth surface of electrolytic copper foil has very low roughness, the reverse-treated copper foil (RTF) obtained after surface treatment on the smooth surface also possesses low roughness.

[0010] Traditional copper foil production processes generally do not introduce micro-roughening additives, resulting in a common problem of large particle size and high profile. The size of these coarsened particles directly affects downstream processing efficiency: larger particles require longer etching times. The larger particle size also increases the risk of copper residue after etching. While higher roughness ensures excellent peel resistance, the skin effect under high roughness has a significant negative impact on signal transmission. Furthermore, the increasing trend towards thinner and lighter end-use products places new and higher demands on the thinner PCB boards. As the dielectric layer thickness of thinner boards decreases, the roughness of the copper foil surface must be as low as possible while maintaining sufficient bonding strength. Summary of the Invention

[0011] The technical problem to be solved by the present invention is to provide a surface treatment method for electrolytic copper foil. The coarsened particles formed on the treated surface by the method significantly increase the specific surface area of ​​the electrolytic copper foil treated surface, thereby enhancing the mechanical bonding effect while also improving the chemical bonding effect.

[0012] This invention provides a method for surface treatment of electrolytic copper foil, comprising:

[0013] (1) Electrochemical polishing pretreatment of the smooth surface of electrolytic green foil was performed using a pulse power supply;

[0014] (2) A roughened underlayer is formed by DC electrochemical deposition assisted by a leveling agent, resulting in an electrolytic copper foil with a roughened underlayer.

[0015] (3) A second roughening layer is formed on the surface of the roughened substrate by pulsed electrochemical deposition assisted by additives;

[0016] (4) Finally, the electrodeposition of a barrier layer and an anti-oxidation layer on the treated and untreated surfaces of the electrolytic copper foil is carried out sequentially by electrochemical deposition, and a silane coupling agent is coated to obtain the finished foil.

[0017] In this process, coarsening particles are formed on the surface of the second coarsening layer.

[0018] The electrochemical polishing pretreatment in step (1) uses H2SO4 and H2O2.

[0019] The electrochemical polishing parameters in step (1) are: duty cycle 25-50%, pulse frequency 2000Hz, and average current density 2.5-7.5A / dm³. 2 .

[0020] The leveling agent in step (2) is one or more of PEG-2000, PEG-1000, PEG-4000, gelatin, collagen, and hydroxyethyl cellulose, and the addition amount is 5-25 ppm.

[0021] The additive in step (3) is one or more of KMnO4, V2O5, Na2WO4, and Ti2(SO4)3, and the amount added is 10-20 ppm.

[0022] Both steps (2) and (3) require curing.

[0023] The barrier layer in step (4) is electrodeposited using an ashing solution, wherein the ashing solution comprises: Zn 2+ Concentration 1.0-2.0 g / L, K4P2O7 concentration 80-100 g / L, pH value 11-12.

[0024] The anti-oxidation layer in step (4) is a chromium-containing treatment layer.

[0025] The average thickness of the roughened underlayer is approximately 0.25 μm, and the thickness of the second roughened layer is approximately 1.25-1.75 μm.

[0026] The coarsened particles are composed of stacked nanoscale structural units, with an average particle size between 1.0 and 2.0 μm and an average particle size of 100-200 nm for each nanoscale structural unit. The coarsened particles are not in direct contact, and some gaps exist between them. The surface area ratio (Sdr) of the treated surface is between 45% and 65%. The root mean square surface roughness (Sq) is between 0.5 and 1.0 μm. The peak density (Spd) is between 35,000 and 45,000 mm². -2 Between 80-120 mm peak curvature (Spc). -1 The ten-point average roughness Rz of the finished foil is between 1.5 and 2.0 μm. The peel strength of a 35 μm RTF copper foil hot-pressed with a halogen-free prepreg at a glass transition temperature of 200°C is between 0.76 and 0.88 kgf / cm. The PCB board made by pressing the finished foil of this invention with PPO resin has an insertion loss of -0.9 to -1.73 dB / inch at 25 GHz.

[0027] The technical solution adopted according to the present invention includes the following steps:

[0028] Step 1: Electrochemical Polishing Pretreatment of the Raw Foil Surface: The smooth surface of the electrolytic raw foil is pretreated with electrochemical polishing using a pulsed power supply. Firstly, through the chemical reaction between H₂SO₄ and CuO and Cu₂(OH)₂CO₃, the oxide layer on the surface of the raw foil is converted into Cu. 2+ Furthermore, under the oxidation of Cu by H2O2 and the electrochemical dissolution of Cu by reverse pulse current, the bright surface of the electrolytic green foil is subjected to micro-etching pretreatment to improve the density of nucleation active sites on the bright surface.

[0029] Step 2: Electrochemical deposition roughening of the underlayer: A positively charged leveling agent is added to the roughening solution to promote electrochemical deposition in the pits of the pretreated smooth surface while inhibiting electrochemical deposition in the protrusions, thereby reducing the adverse effects of the roughness of the treated surface on subsequent roughening.

[0030] Step 3: Pulsed Electrochemical Deposition of the Second Coarsening Layer: Under the same average current density conditions, the peak current density in pulsed electrodeposition is much higher than that in direct current electrodeposition. The higher current density effectively increases electrochemical polarization during the electrodeposition process, which is beneficial for accelerating crystal nucleus formation and thus achieving grain refinement. Simultaneously, an appropriate duty cycle during pulsed electrodeposition can effectively replenish the ion concentration on the electrode surface, helping to reduce the adverse effects of concentration polarization on electrochemical deposition. The addition of inorganic additives can inhibit the excessive growth of dendritic coarsening structures during electrodeposition, thereby reducing the size of the coarsened particles.

[0031] Step 4: Pulse Electrochemical Deposition of Barrier and Anti-oxidation Layers: The hot-pressing process between the electrolytically treated copper foil and the prepreg requires a barrier layer to prevent chemical reactions between the copper layer and the resin, ensuring the bonding strength between the copper foil and the prepreg. Electrochemical deposition of a chromium-containing treatment layer can improve the oxidation resistance of the copper foil at room temperature. Pulse electrochemical deposition not only effectively improves the density of the plating but also increases the hydroxyl content on the surface of the treatment layer. Increased hydroxyl content on the treatment layer surface enhances the chemical bonding density with the silane coupling agent, which is beneficial for improving the chemical adhesion of the copper foil treatment surface.

[0032] Step 5: Silane Coupling Agent Coating: Besides the mechanical anchoring between the copper foil and resin, the chemical interaction between the silane coupling agent on the copper foil surface and the resin also plays a crucial role in the bonding between the electrolytic copper foil and the prepreg. During surface treatment, a certain number of hydroxyl groups (Cu-OH) are formed on the copper foil surface. After hydrolysis of the silane coupling agent, a large number of silanol groups (Si-OH) are formed. Under heating conditions, Cu-OH and Si-OH can undergo a condensation reaction, producing a Cu-O-Si chemical bond, thereby improving the bonding strength between the electrolytic copper foil and the prepreg.

[0033] Beneficial effects

[0034] The coarsened particles formed on the treated surface by the method of this invention significantly increase the specific surface area of ​​the electrolytic copper foil, enhancing both mechanical and chemical bonding. Electrolytic copper foil produced by this method has a surface roughness Rz not exceeding 2.0 μm, a root mean square surface roughness Sq not exceeding 1.0 μm, an interface expansion area ratio Sdr > 40%, and a peak curvature Spc > 80 mm. -1 Peak density Spd > 30000 mm -2 This method improves the surface roughness, peel resistance, and signal transmission performance of electrolytic copper foil to a certain extent. The peel strength of a 35μm finished foil laminated with a prepreg at a glass transition temperature of 200℃ is >0.76 kgf / cm. When copper foil produced by the method provided in this invention is laminated with polyphenylene ether resin to form a copper-clad laminate, the insertion loss of the resulting PCB material at 25GHz can reach -0.9 dB / inch. Attached Figure Description

[0035] Figure 1 The image shows an SEM image of an electrolytic copper foil processed by the method of this invention.

[0036] Figure 2 For comparison of laser confocal images of Comparative Example 1 and Example 1;

[0037] Figure 3This is a schematic diagram of the surface structure of the electrolytic copper foil of the present invention; wherein, 1 is the roughening underlayer, 2 is the second roughening layer, and 3 is the roughening particles with special morphology. Detailed Implementation

[0038] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0039] Hot lamination of copper-clad laminates: First, referring to a "sandwich" structure, the produced electrolytic copper foil and prepreg are stacked (four prepregs with a glass transition temperature of 200℃ are placed between the upper and lower copper foils). Then, hot lamination is performed under certain pressure and temperature, with the hot lamination temperature between 220-250℃ and the surface pressure between 20-25 kg / m². 2 The time is between 90 and 150 minutes.

[0040] Peel strength test: First, use a cutter to cut the hot-pressed copper-clad laminate into strips with a width of 3.0mm; then, use a utility knife to peel off 1-2cm of copper foil from one side of the copper-clad laminate, and fix the peeled copper foil to one end of a weight; finally, use the peel strength tester to move the weight to move the copper foil to perform the peel strength test.

[0041] Transmission Characteristic Testing: Samples for transmission characteristic testing were fabricated using hot-pressed copper-clad laminates, and transmission loss was measured in the high-frequency bandwidth. In evaluating transmission characteristics, the stripline resonator method (a method for measuring S21 parameters in a microstrip structure with an electrolyte thickness of 50 μm, conductor length of 1.0 mm, conductor thickness of 18 μm, conductor circuit width of 120 μm, characteristic impedance of 50 Ω, and without a capping film) suitable for bandwidths from 1 GHz to 25 GHz was used to measure transmission loss at 25 GHz. Each sample was tested five times, and the average of the five tests was taken as the final test result for that sample. A higher transmission loss corresponds to a larger negative absolute value.

[0042] Example 1

[0043] This embodiment provides a surface treatment method for electrolytic copper foil, the details of which are as follows:

[0044] The thickness is selected as 35μm, the surface roughness is Rz≤5.5μm, Ra≤0.25μm, and the surface density is 275±5g / m³. 2 The electrolytic green foil is processed sequentially as follows:

[0045] S1. Electrochemical polishing pretreatment

[0046] Electrolytic green foil is fed into a pretreatment tank, where the copper foil surface is micro-etched by the chemical reaction between the pretreatment solution and the oxides on the copper foil surface, as well as by the dissolution effect of the reverse pulse current on the copper layer.

[0047] The parameters in the electrochemical polishing pretreatment process are as follows:

[0048] Duty cycle: 25%

[0049] Pulse frequency: 2000Hz

[0050] Average current density: 5.0 A / dm 2

[0051] H2SO4 concentration: 100g / L

[0052] H2O2 concentration: 30wt%

[0053] Pretreatment solution temperature: 30℃

[0054] The pretreatment liquid flow rate is 2.5 m³ / h. 3 / h;

[0055] Pretreatment time: 10sS2. Additive-assisted DC electrochemical deposition for rough underlayer preparation.

[0056] The pretreated copper foil is transferred to an electrolytic cell containing additives for electrochemical deposition to roughen the underlayer. The specific parameters during the electrochemical deposition process are as follows:

[0057] Cu 2+ Ion concentration: 15 g / L

[0058] H2SO4 concentration: 150g / L

[0059] Polyethylene glycol PEG-2000 concentration: 25 ppm

[0060] Cl - Ion concentration: 10 ppm

[0061] Electrolyte temperature: 30℃

[0062] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0063] Current density: 10A / dm 2

[0064] Processing time: 10sS3. DC electrochemical deposition and curing to form the underlayer.

[0065] After the electrochemical deposition roughening layer is completed, the electrolytic copper foil is washed with water, squeezed dry, and then transferred to a curing tank for curing. The specific parameters for the curing stage are as follows:

[0066] Cu 2+ Ion concentration: 45 g / L

[0067] H2SO4 concentration: 100g / L

[0068] Curing solution temperature: 50℃

[0069] Curing fluid flow rate: 10.0 m³ / h 3 / h

[0070] Curing current density: 25A / dm 2

[0071] Processing time: 10sS4. Additive-assisted pulsed electrochemical deposition of the second roughening layer.

[0072] The copper foil, after electrochemical deposition and coarse curing of the underlayer, is then placed in an electrolytic cell containing additives for a secondary roughening treatment. The specific parameters of the second roughened layer are as follows:

[0073] Cu 2+ Ion concentration: 15 g / L

[0074] H2SO4 concentration: 150g / L

[0075] KMnO4 concentration: 20ppm

[0076] Electrolyte temperature: 30℃

[0077] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0078] Average current density: 20A / dm 2

[0079] Duty cycle: 25%

[0080] Pulse frequency: 100Hz

[0081] Processing time: 10s

[0082] S5. DC electrochemical deposition and curing for the underlayer.

[0083] To prevent the second roughening layer from peeling off, it needs to be cured. Under the action of direct current, a curing layer is electrochemically deposited on the surface of the second roughening layer according to the process parameters of S3.

[0084] S6. Pulse electrochemical deposition barrier layer

[0085] After curing, the copper foil is washed with water and squeezed dry before entering an ashing tank for electrochemical deposition of the barrier layer. Specific parameters for the ashing stage are as follows:

[0086] Zn2+ Ion concentration: 1.0 g / L

[0087] K4P2O7 concentration: 80 g / L

[0088] pH value: 11

[0089] ashing solution temperature: 35℃

[0090] Ashing liquid flow rate: 2.5m 3 / h

[0091] Average current density per dm²: 2.0 A / dm² 2

[0092] Processing surface duty cycle: 33%

[0093] Processing surface pulse frequency: 1000Hz

[0094] Average current density on untreated surface: 1.5 A / dm 2

[0095] Non-processed surface duty cycle: 25%

[0096] Non-processed surface pulse frequency: 2000Hz

[0097] Processing time: 10sS7. Pulse electrochemical deposition of anti-oxidation layer

[0098] After ashing, the electrolytic copper foil is washed with water, squeezed dry, and then placed in a passivation tank for electrochemical deposition of an anti-oxidation layer. The parameters for the passivation stage are as follows:

[0099] Cr(VI) concentration: 1.0 g / L

[0100] pH value: 11.5

[0101] Passivation solution temperature: 35℃

[0102] Passivation fluid flow rate: 2.5m 3 / h

[0103] Average current density per dm²: 2.5 A / dm² 2

[0104] Processing surface duty cycle: 33%

[0105] Processing surface pulse frequency: 1000Hz

[0106] Average current density on untreated surface: 8.0 A / dm 2

[0107] Non-processed surface duty cycle: 25%

[0108] Non-processed surface pulse frequency: 2000Hz

[0109] Processing time: 10sS8. Silane coupling agent coating

[0110] After passivation, the copper foil is washed with water, squeezed dry, and then coated with a silane coupling agent. The specific parameters for the silane coupling agent coating stage are as follows:

[0111] Silane coupling agent name: 3-(methacryloyloxy)propyltrimethoxysilane (KBM-503)

[0112] The concentration of the silane coupling agent is 0.25 g / L.

[0113] Silane coupling agent aqueous solution temperature: 30℃

[0114] Flow rate of silane coupling agent aqueous solution: 2.5m 3 / h

[0115] Oven temperature setting: 200℃.

[0116] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.73 μm, root mean square surface roughness Sq is 0.55 μm, interface expansion area ratio Sdr is 58.65%, and peak curvature Spc is 105 mm. -1 The peak density Spd is 39600 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.88 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin, when processed into a PCB board at 25 GHz, is -0.93 dB / inch.

[0117] Example 2

[0118] The difference between this embodiment and Embodiment 1 is that the pulse current parameters in the pretreatment process and the additives and concentrations used in the coarsening and undercoating electrochemical deposition process were adjusted. (1) The duty cycle of the pulse current in the pretreatment process was adjusted to 33%, and the average current density was adjusted to 2.5 A / m. 2 (2) Replace the additives used in the roughening and electrochemical deposition of the bottom layer with gelatin and adjust the concentration to 10 ppm.

[0119] S1. The specific parameters for the electrochemical polishing pretreatment are as follows:

[0120] Duty cycle: 33%

[0121] Pulse frequency: 2000Hz

[0122] Average current density: 2.5 A / dm 2

[0123] H2SO4 concentration: 100g / L

[0124] H2O2 concentration: 30wt%

[0125] Pretreatment solution temperature: 30℃

[0126] The pretreatment liquid flow rate is 2.5 m³ / h. 3 / h;

[0127] Preprocessing time: 10s

[0128] The specific parameters for S2. Additive-assisted DC electrochemical deposition for rough underlayer preparation are as follows:

[0129] Cu 2+ Ion concentration: 15 g / L

[0130] H2SO4 concentration: 150g / L

[0131] Gelatin concentration: 10 ppm

[0132] Cl - Ion concentration: 10 ppm

[0133] Electrolyte temperature: 30℃

[0134] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0135] Current density: 10A / dm 2

[0136] Processing time: 10s

[0137] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.95 μm, root mean square surface roughness Sq is 0.91 μm, interface expansion area ratio Sdr is 60.23%, and peak curvature Spc is 120 mm. -1 The peak density Spd is 45000 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.81 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin, when processed into a PCB board at 25 GHz, is -1.16 dB / inch.

[0138] Example 3

[0139] The difference between this embodiment and Embodiment 1 is that the pulse current parameters in the pretreatment process and the additives and concentrations used in the electrochemical deposition of the second roughening layer were adjusted. (1) The duty cycle of the pulse current in the pretreatment process was adjusted to 50%, and the average current density was adjusted to 7.5 A / m. 2 (2) Replace the additive used in the electrochemical deposition of the second roughening layer with V2O5 and adjust the concentration to 10ppm.

[0140] S1. The specific parameters for the electrochemical polishing pretreatment are as follows:

[0141] Duty cycle: 50%

[0142] Pulse frequency: 2000Hz

[0143] Average current density: 7.5 A / m 2

[0144] H2SO4 concentration: 100g / L

[0145] H2O2 concentration: 30wt%

[0146] Pretreatment solution temperature: 30℃

[0147] The pretreatment liquid flow rate is 2.5 m³ / h. 3 / h;

[0148] Preprocessing time: 10s

[0149] The specific parameters for the additive-assisted pulsed electrochemical deposition of the second roughening layer are as follows:

[0150] Cu 2+ Ion concentration: 15 g / L

[0151] H2SO4 concentration: 150g / L

[0152] V2O5 concentration: 10ppm

[0153] Electrolyte temperature: 30℃

[0154] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0155] Average current density: 20A / dm 2

[0156] Duty cycle: 25%

[0157] Pulse frequency: 100Hz

[0158] Processing time: 10s

[0159] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.87 μm, root mean square surface roughness Sq is 0.84 μm, interface expansion area ratio Sdr is 54.69%, and peak curvature Spc is 112 mm. -1 The peak density Spd is 41500 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.76 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin as raw material for processing into a PCB board at 25 GHz is -1.65 dB / inch.

[0160] Example 4

[0161] The difference between this embodiment and Embodiment 1 lies in the adjustment of the additives and concentrations used in the roughening underlayer and the second roughening layer electrochemical deposition process. (1) The additive used in the roughening underlayer electrochemical deposition was replaced with collagen, and the concentration was adjusted to 15 ppm; (2) The additive used in the second roughening layer electrochemical deposition was replaced with Na2WO4, and the concentration was adjusted to 20 ppm. S2. The specific parameters of the additive-assisted DC electrochemical deposition roughening underlayer are as follows:

[0162] Cu 2+ Ion concentration: 15 g / L

[0163] H2SO4 concentration: 150g / L

[0164] Collagen concentration: 15ppm

[0165] Cl - Ion concentration: 10 ppm

[0166] Electrolyte temperature: 30℃

[0167] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0168] Current density: 10A / dm 2

[0169] Processing time: 10s

[0170] The specific parameters for the additive-assisted pulsed electrochemical deposition of the second roughening layer are as follows:

[0171] Cu 2+ Ion concentration: 15 g / L

[0172] H2SO4 concentration: 150g / L

[0173] Na2WO4 concentration: 20ppm

[0174] Electrolyte temperature: 30℃

[0175] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0176] Average current density: 20A / dm 2

[0177] Duty cycle: 25%

[0178] Pulse frequency: 100Hz

[0179] Processing time: 10s

[0180] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.91 μm, root mean square surface roughness Sq is 0.89 μm, interface expansion area ratio Sdr is 64.91%, and peak curvature Spc is 115 mm. -1 The peak density Spd is 43700 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.83 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin as raw material for processing into a PCB board at 25 GHz is -1.58 dB / inch.

[0181] Example 5

[0182] The difference between this embodiment and Embodiment 1 lies in the adjustment of the additives and concentrations used in the electrochemical deposition of the roughening underlayer and the second roughening layer. (1) The additive used in the electrochemical deposition of the roughening underlayer is replaced with HEC, and the concentration is adjusted to 10 ppm; (2) The additive used in the electrochemical deposition of the second roughening layer is replaced with Ti2(SO4)3, and the concentration is adjusted to 10 ppm. S2. The specific parameters of the additive-assisted DC electrochemical deposition of the roughening underlayer are as follows:

[0183] Cu 2+ Ion concentration: 15 g / L

[0184] H2SO4 concentration: 150g / L

[0185] HEC concentration: 10 ppm

[0186] Cl - Ion concentration: 10 ppm

[0187] Electrolyte temperature: 30℃

[0188] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0189] Current density: 10A / dm 2

[0190] Processing time: 10s

[0191] The specific parameters for the additive-assisted pulsed electrochemical deposition of the second roughening layer are as follows:

[0192] Cu 2+ Ion concentration: 15 g / L

[0193] H2SO4 concentration: 150g / L

[0194] Ti2(SO4)3 concentration: 10 ppm

[0195] Electrolyte temperature: 30℃

[0196] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0197] Average current density: 20A / dm 2

[0198] Duty cycle: 25%

[0199] Pulse frequency: 100Hz

[0200] Processing time: 10s

[0201] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.83 μm, root mean square surface roughness Sq is 0.85 μm, interface expansion area ratio Sdr is 52.30%, and peak curvature Spc is 108 mm. -1 The peak density Spd is 40300 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.79 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin, when processed into a PCB board at 25 GHz, is -1.73 dB / inch.

[0202] Example 6

[0203] The difference between this embodiment and Example 1 is that the pulse current parameters in the pretreatment process and the additives and concentrations used in the roughening and underlayment electrochemical deposition process were adjusted. (1) The duty cycle of the pulse current in the pretreatment process was adjusted to 33%, and the pulse frequency was adjusted to 100Hz; (2) The additives used in the roughening and underlayment electrochemical deposition were replaced with polyethylene glycol with a molecular weight of 1000 and the concentration was adjusted to 5ppm.

[0204] S1. The specific parameters for the electrochemical polishing pretreatment are as follows:

[0205] Duty cycle: 33%

[0206] Pulse frequency: 100Hz

[0207] Average current density: 5.0 A / dm 2

[0208] H2SO4 concentration: 100g / L

[0209] H2O2 concentration: 30wt%

[0210] Pretreatment solution temperature: 30℃

[0211] The pretreatment liquid flow rate is 2.5 m³ / h. 3 / h;

[0212] Preprocessing time: 10s

[0213] The specific parameters for S2. Additive-assisted DC electrochemical deposition for rough underlayer preparation are as follows:

[0214] Cu 2+ Ion concentration: 15 g / L

[0215] H2SO4 concentration: 150g / L

[0216] PEG-1000 concentration: 5 ppm

[0217] Cl - Ion concentration: 10 ppm

[0218] Electrolyte temperature: 30℃

[0219] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0220] Current density: 10A / dm 2

[0221] Processing time: 10s

[0222] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.79 μm, root mean square surface roughness Sq is 0.73 μm, interface expansion area ratio Sdr is 49.28%, and peak curvature Spc is 98 mm. -1 The peak density Spd is 38800 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.80 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin, when processed into a PCB board at 25 GHz, is -1.61 dB / inch.

[0223] Example 7

[0224] The difference between this embodiment and Example 1 is that the additives and concentrations used in the electrochemical deposition of the roughening underlayer and the second roughening layer were adjusted. (1) The additive used in the electrochemical deposition of the roughening underlayer was replaced with polyethylene glycol with a molecular weight of 4000 and the concentration was adjusted to 20 ppm; (2) The additive used in the electrochemical deposition of the second layer was replaced with Ti2(SO4)3 and the concentration was adjusted to 10 ppm.

[0225] The specific parameters for S2. Additive-assisted DC electrochemical deposition for rough underlayer preparation are as follows:

[0226] Cu 2+ Ion concentration: 15 g / L

[0227] H2SO4 concentration: 150g / L

[0228] PEG-4000 concentration: 20ppm

[0229] Cl - Ion concentration: 10 ppm

[0230] Electrolyte temperature: 30℃

[0231] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0232] Current density: 10A / dm 2

[0233] Processing time: 10s

[0234] The specific parameters for the additive-assisted pulsed electrochemical deposition of the second roughening layer are as follows:

[0235] Cu 2+ Ion concentration: 15 g / L

[0236] H2SO4 concentration: 150g / L

[0237] Ti2(SO4)3 concentration: 10 ppm

[0238] Electrolyte temperature: 30℃

[0239] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0240] Average current density: 20A / dm 2

[0241] Duty cycle: 25%

[0242] Pulse frequency: 100Hz

[0243] Processing time: 10s

[0244] Example Results: The finished foil processed using the parameters in this example exhibits low profile: linear roughness Rz is 1.85 μm, root mean square surface roughness Sq is 0.78 μm, interface expansion area ratio Sdr is 56.58%, and peak curvature Spc is 103 mm. -1 The peak density Spd is 38500 mm. -2 The peel strength of the finished foil produced using the parameters of this embodiment, after being laminated with a prepreg (Tg 200℃), is 0.81 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using the parameters of this embodiment with polyphenylene ether resin, when processed into a PCB board at 25 GHz, is -1.67 dB / inch.

[0245] Comparative Example 1

[0246] The difference between this comparative example and Example 1 is that the pretreatment method for the green foil was adjusted. A chemical bath was used to pretreat the electrolytic green foil to remove the oxide layer and impurities from the copper foil surface.

[0247] S1. The specific parameters for chemical bath pretreatment are as follows:

[0248] H2SO4 concentration: 100g / L

[0249] H2O2 concentration: 30wt%

[0250] Pretreatment solution temperature: 30℃

[0251] The pretreatment liquid flow rate is 2.5 m³ / h. 3 / h;

[0252] Preprocessing time: 10s

[0253] Comparative Example Results: The finished foil processed using these comparative parameters exhibits lower profile characteristics: linear roughness Rz is 2.37 μm, root mean square surface roughness Sq is 1.54 μm, interface expansion area ratio Sdr is 58.37%, and peak curvature Spc is 76 mm. -1 The peak density Spd is 32100 mm. -2 The peel strength of the finished foil produced using these comparative parameters, after being laminated with a prepreg (Tg 200℃), is 0.63 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using these comparative parameters with polyphenylene ether resin as raw material for processing into a PCB board at 25 GHz is -2.49 dB / inch.

[0254] Comparative Example 2

[0255] The difference between this comparative example and Comparative Example 1 is that no additional additives are introduced during the roughening and undercoating electrochemical deposition process; instead, a CuSO4 solution containing H2SO4 is used directly for DC electrodeposition.

[0256] The specific parameters for S2. DC electrochemical deposition for rough underlayer preparation are as follows:

[0257] Cu 2+ Ion concentration: 15 g / L

[0258] H2SO4 concentration: 150g / L

[0259] Electrolyte temperature: 30℃

[0260] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0261] Current density: 10A / dm 2

[0262] Processing time: 10s

[0263] Example Results: The finished foil processed using these comparative parameters exhibits low profile: linear roughness Rz is 2.62 μm, root mean square surface roughness Sq is 1.77 μm, interface expansion area ratio Sdr is 62.34%, and peak curvature Spc is 88 mm. -1 The peak density Spd is 35500 mm. -2 The peel strength of the finished foil produced using these comparative parameters, after being laminated with a prepreg (Tg 200℃), is 0.65 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using these comparative parameters with polyphenylene ether resin as raw material for processing into a PCB board at 25 GHz is -3.18 dB / inch.

[0264] Comparative Example 3

[0265] The difference between this comparative example and Comparative Example 1 is that no additives are used during the electrochemical deposition of the second roughening layer.

[0266] S4. The specific parameters for the pulsed electrochemical deposition of the second roughening layer are as follows:

[0267] Cu 2+ Ion concentration: 15 g / L

[0268] H2SO4 concentration: 150g / L

[0269] Electrolyte temperature: 30℃

[0270] Roughening fluid flow rate: 5.0 m³ / h 3 / h

[0271] Average current density: 20A / dm2

[0272] Duty cycle: 25%

[0273] Pulse frequency: 100Hz

[0274] Processing time: 10s

[0275] Example Results: The finished foil processed using these comparative parameters exhibits low profile: linear roughness Rz is 2.23 μm, root mean square surface roughness Sq is 1.38 μm, interface expansion area ratio Sdr is 50.19%, and peak curvature Spc is 81 mm. -1 The peak density Spd is 33400 mm. -2 The peel strength of the finished foil produced using these comparative parameters, after being laminated with a prepreg (Tg 200℃), is 0.58 kgf / cm. The insertion loss of the copper-clad laminate formed by laminating the copper foil produced using these comparative parameters with polyphenylene ether resin as raw material for processing into a PCB board at 25 GHz is -2.74 dB / inch.

[0276] Table 1 lists the surface treatment parameters and performance indicators of the finished foil in different embodiments and comparative examples. From this table, it can be seen that both the method provided by this invention and conventional surface treatment methods can produce electrolytic copper foil with low roughness, high peel strength, and excellent signal transmission performance. Electrolytic green foil of the same specifications can achieve a lower profile (roughness Rz reduced by approximately 27%), higher peel strength (peel strength increased by approximately 39.7%), and superior signal transmission performance (insertion loss reduced by approximately 62.7%) compared to conventional electrolytic copper foil using the surface treatment method provided by this invention.

[0277] To more intuitively illustrate the implementation effects of this invention, the microstructure of the samples produced in the examples was observed using a field emission scanning electron microscope (FE-SEM). Figure 1 It can be clearly observed that a large number of fine pineapple-shaped coarsened particles are formed on the surface of the electrolytic copper foil. Further, under high magnification, it can be found that the coarsened structure is composed of nanoscale structural units. Figure 2 The images shown are laser confocal images of Comparative Example 1 and Example 1. It can be observed from the images that the copper foil produced by this invention has a relatively low roughness, with Rz not exceeding 2.0 μm. The coarsened particles are small in size, and there are numerous gaps between the particles. These gaps between the particles effectively enhance the mechanical bonding between the copper foil and the substrate. The irregular shape effectively increases the specific surface area of ​​the coarsened structure, which is beneficial for increasing the amount of silane coupling agent adhered per unit area, laying the foundation for improved chemical bonding.

[0278] Finally, it should be emphasized that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

[0279] Table 1. Comparison of surface treatment parameters and finished foil performance indicators of different embodiments and comparative examples

[0280]

[0281]

Claims

1. A method for surface treatment of electrolytic copper foil, comprising: (1) The smooth surface of the electrolytic green foil is pretreated by electrochemical polishing using a pulse power supply; wherein, the electrochemical polishing pretreatment uses H2SO4 and H2O2; the electrochemical polishing parameters are: duty cycle 25-50%, pulse frequency 2000 Hz, average current density 2.5-7.5 A / dm³. 2 ; (2) A roughened underlayer is formed by DC electrochemical deposition assisted by a leveling agent to obtain an electrolytic copper foil with a roughened underlayer; wherein the leveling agent is PEG-2000; (3) A second roughening layer is formed on the surface of the roughened substrate by pulsed electrochemical deposition assisted by an additive; wherein the additive is KMnO4; (4) Finally, the electrodeposition of a barrier layer and an anti-oxidation layer on the treated and untreated surfaces of the electrolytic copper foil is carried out sequentially by electrochemical deposition, and a silane coupling agent is coated to obtain the finished foil; In this process, coarsened particles are formed on the surface of the finished foil; the coarsened particles are formed by the stacking of nanoscale structural units, the average particle size of the coarsened particles is between 1.0 and 2.0 μm, and the average particle size of the nanoscale structural units is between 100 and 200 nm.

2. The method according to claim 1, characterized in that: The amount of leveling agent added in step (2) is 5-25 ppm.

3. The method according to claim 1, characterized in that: The amount of additive added in step (3) is 10-20 ppm.

4. The method according to claim 1, characterized in that: Both steps (2) and (3) require curing.

5. The method according to claim 1, characterized in that: The barrier layer in step (4) is electrodeposited using an ashing solution, wherein the ashing solution comprises: Zn 2+ Concentration 1.0-2.0 g / L, K4P2O7 concentration 80-100 g / L, pH value 11-12.

6. The method according to claim 1, characterized in that: The anti-oxidation layer in step (4) is a chromium-containing treatment layer.

Citation Information

Patent Citations

  • Black surface treatment process of electrolytic copper foil

    CN101906630A

  • Manufacturing process of smooth roughened electrolytic copper foil

    CN102277605A

  • Additive used for electrolytic copper foil and surface roughening treatment technology for electrolytic copper foil

    CN104404590A

  • Surface roughening and curing treatment method of RTF copper foil for high-frequency copper-clad plate

    CN112921371A